Salmonella enterica serovar Typhi H58 clone has been endemic in Zimbabwe from 2012 to 2019. (21st December 2020) - Mashe, Tapfumanei; Leekitcharoenphon, Pimlapas; Mtapuri-Zinyowera, Sekesai; Kingsley, Robert A; Robertson, V; Tarupiwa, Andrew; Kock, Marleen M; Makombe, Evidence P; Chaibva, Blessmore V; Manangazira, Portia; Phiri, Isaac; Nyadundu, Simon; et al.
Abstract: Background: Typhoid fever, caused by S. enterica ser . Typhi, continues to be a substantial health burden in developing countries. Little is known of the genotypic diversity of S. enterica ser . Typhi in Zimbabwe, but this is key for understanding the emergence and spread of this pathogen and devising interventions for its control. Objectives: To report the molecular epidemiology of S. enterica ser . Typhi outbreak strains circulating from 2012 to 2019 in Zimbabwe, using comparative genomics. Methods: A review of typhoid cases records from 2012 to 2019 in Zimbabwe was performed. The phylogenetic relationship of outbreak isolates from 2012 to 2019 and emergence of antibiotic resistance was investigated by whole-genome sequence analysis. Results: A total 22 479 suspected typhoid cases, 760 confirmed cases were reported from 2012 to 2019 and 29 isolates were sequenced. The majority of the sequenced isolates were predicted to confer resistance to aminoglycosides, β-lactams, phenicols, sulphonamides, tetracycline and fluoroquinolones (including qnrS detection). The qnrS1 gene was associated with an IncN (subtype PST3) plasmid in 79% of the isolates. Whole-genome SNP analysis, SNP-based haplotyping and resistance determinant analysis showed that 93% of the isolates belonged to a single clade represented by multidrug-resistant H58 lineage I (4.3.1.1), with a maximum pair-wise distance of 22 SNPs. Conclusions: This study has provided detailed genotypic characterization of the outbreak strain, identified as S . Typhi 4.3.1.1 (H58). The strain has reduced susceptibility to ciprofloxacin due to qnr S carried by an IncN (subtype PST3) plasmid resulting from ongoing evolution to full resistance.